"Disease-modifying" drugs in rheumatoid arthritis. Issue 26 (30th December 1985) - Unknown
Abstract : Rheumatoid arthritis (RA) is a systemic inflammatory disease whose major feature is a destructive peripheral polyarthritis. In this condition simple analgesics may relieve pain while non-steroidal anti-inflammatory drugs (NSAIDs) can reduce swelling and stiffness; neither however change the activity or rate of progression of the disease. 1 If these drugs fail to control symptoms, if there is radiological evidence of rapid or progressive joint damage, or if the patient has serious extra-articular manifestations of RA (e.g. lung disease, vasculitis, amyloidosis), it is usual to start a drug that might modify the disease or induce remission. This article discusses disease-modifying drugs (DMDs) and how to choose between them.